2016
DOI: 10.1155/2016/6305735
|View full text |Cite
|
Sign up to set email alerts
|

The SGLT-2 Inhibitor Dapagliflozin Has a Therapeutic Effect on Atherosclerosis in Diabetic ApoE−/−Mice

Abstract: Background. Our study aimed to observe the effect of sodium glucose cotransporter-2 (SGLT2) inhibitor dapagliflozin on diabetic atherosclerosis and investigate the subsequent mechanism. Methods. Aortic atherosclerosis was induced in streptozotocin induced diabetic ApoE−/− mice by feeding with high-fat diet, and dapagliflozin was administrated intragastrically for 12 weeks as treatment. Effects of dapagliflozin on indices of glucose and fat metabolism, IL-1β, IL-18, NLRP3 protein levels, and the reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
156
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 34 publications
9
156
0
3
Order By: Relevance
“…[ 52 ] Moreover, the treatment of insulin‐resistant diabetic rats with DAPA or LPZ reduced the serum levels of FFAs, thereby contributing to the insulin‐sensitizing effects of both tested compounds. These results are in agreement with those shown by the previous study [ 53 ] that reported that treatment with DAPA significantly lowered the FFAs levels in diabetic ApoE −/− mice. To the best of our knowledge, the effect of LPZ on FFAs levels has not been previously demonstrated.…”
Section: Discussionsupporting
confidence: 94%
“…[ 52 ] Moreover, the treatment of insulin‐resistant diabetic rats with DAPA or LPZ reduced the serum levels of FFAs, thereby contributing to the insulin‐sensitizing effects of both tested compounds. These results are in agreement with those shown by the previous study [ 53 ] that reported that treatment with DAPA significantly lowered the FFAs levels in diabetic ApoE −/− mice. To the best of our knowledge, the effect of LPZ on FFAs levels has not been previously demonstrated.…”
Section: Discussionsupporting
confidence: 94%
“…DAPA-mediated attenuation of TNFα-induced NFκB mRNA expression implicates DAPA in transcriptional regulation, a novel observation, and in keeping with recently identified 'off target' effects involving activation of cell signalling pathways independent of SGLT-2 by other members of the SGLT-2 class of agents. 5,15 Endothelial cell dysfunction is identified as a significant contributor to early atherogenesis particularly in the vulnerable type 2 diabetic patient population. 16,17 Upregulation of adhesion molecule expression is a marker of endothelial cell dysfunction and a precursor to the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent pre-clinical studies support our preliminary observations with identification of reduced atherosclerotic burden in diabetic ApoE −/− mice treated with DAPA with no significant reductions in non-diabetic ApoE −/− mice. 4,5 However, in vitro and in vivo attenuation in vascular peptide expression, improvements in endothelial function, non-significant reductions in weight together with previously documented attenuation of expression of inflammatory mediators and molecules including NFκB and interleukin-1 (IL-1)β in the non-diabetic ApoE −/− mouse model 5 may all combine to produce reductions in atherosclerotic disease burden over extended time periods independently of improvements in hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Dapagliflozin also reduces aortic macrophages infiltration and ROS generation and favours atherosclerotic plaque stabilization. In vitro , dapagliflozin reduces inflammasome activation and decreases IL‐1β release in bone marrow‐derived macrophages stimulated with high concentrations of glucose and lipids .…”
Section: The Impact Of Antidiabetic Drugs On Endothelial Dysfunctionmentioning
confidence: 99%
“…Similarly, Leng et al . observed that ApoE −/− mice treated for 12 weeks with dapagliflozin exhibit less vascular inflammation due to reduced plasma concentrations and vascular expression of the inflammasome components, such as nucleotide‐binding oligomerization domain‐like receptor 3 (NLRP3), IL‐1β and IL‐18. Dapagliflozin also reduces aortic macrophages infiltration and ROS generation and favours atherosclerotic plaque stabilization.…”
Section: The Impact Of Antidiabetic Drugs On Endothelial Dysfunctionmentioning
confidence: 99%